Guardare al mondo da una provincia di frontiera. Arriano e la scienza politica degli antichi (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2021)
The  wreck  of  the  ancient  literature  on  war  is  well  known  but  it  represents  nevertheless  a  huge problem for modern historiography. Surviving manuals, strategemata and even historical works that describe  wars  and  battles  are  therefore  texts  of  immense  value  to  understand  the  ancient  war science, but very few documents  transmit the point of view of ancient commanders. In this sense, the “tryptic” formed by three texts of Arrian’s literary production represents a witness of immense value. Arrian  was  appointed  as  governor  of  Cappadocia  by  Hadrian  during  a  troubled  moment  for  the Roman east. In particular, he had to face a possible invasion of the Sarmatian tribes from the east. The Periplus Ponti Euxini, the Acies contra Alanos and the Taktikà formed therefore a textual unity for historical and conceptual reasons. The present contribution proposes an analysis of the ‘tryptic’ from multiple perspectives and through different approaches. The Periplus Ponti Euxini in particular is analysed in its relation with the other texts, highlighting its cultural, historical and political context.
Keywords: Arrian; ancient war literature; historiography